Brand equity: A review and application of different brand valuation approaches in South Africa - Reyneke, Johan (My University, 2014)
The value of a brand can be difficult to measure since it is an intangible asset and it is only since the early 1980s that brand valuation has gained importance in terms of inclusion in business valuation (Kapferer, 1997). As brand valuation has become more acceptable Wyner (2001) has raised some concerns regarding the use of the correct model for the correct purpose during calculations. With twenty-two brand valuation approaches highlighted by Abratt and Bick (2003) it can be difficult for marketers to know which approach is suitable for their specific objective. This study reviewed different methods of measuring brand equity in an organisation in a South African context and evaluated the suitability of various brand equity valuation approaches to specific brand valuation objectives. Data was collected using the financial statements for the case site and by conducting semi-structured interviews to, in part, explore brand valuation objectives and brand valuation approach selection. This study confirmed the role of the brand as a resource that can provide a firm with a sustained competitive advantage. It was found that the brand is a valuable asset to firms and brand equity a measure of the value added by the brand. The study found that different brand valuation objectives influence the selection of a brand valuation approach. This study provides a guide in terms of available brand valuation approaches categorised by broad brand valuation objectives and provides a process for South African firms to follow when attempting brand valuation.
MBA thesis
Keywords: Brand equity; Marketing; Brand valuation